Self-regulated learning and problem-solving skills in sixth grade students at Ekayana Ehipassiko School South Tangerang - Ika Purnama Sari; Susanto Susanto; Vike Aprilianin Marwintaria Saputri (Universitas Sebelas Maret, 2025)
Higher education plays an important role in shaping students' skills, character, and morals. Thus, there is a relationship between students' level of self-regulated learning and their problem-solving abilities. Students with a high level of self-regulated learning tend to have better problem-solving abilities than students with moderate or low levels of self-regulated learning. With self-regulated learning, students can be more independent in the learning process and able to overcome obstacles that may arise when solving problems. This study focuses on sixth-grade students at Ekayana Ehipassiko School BSD City, South Tangerang. This study uses a survey method with a quantitative approach. The data collection technique uses a questionnaire with a Likert scale. The research population included 44 respondents who were sampled from a population using a questionnaire as a data collection tool, which was carefully designed and in accordance with a quantitative approach to measure the level of influence between the two variables. In this study, there was one independent variable, namely self-regulated learning, and one dependent variable, namely problem solving in students. The results of this study show a positive and significant influence of 77.3% between the variable of self-regulated learning and the variable of problem solving in students. The magnitude of this influence can be seen from the results of a simple linear test which found a deterministic R square value of 0.773, which means that self-regulated learning influences problem solving and the remaining 22.7% is influenced by other factors.